Price Discount Framing: How it Can Increase the Purchase Intention? - Gede Widiadnyana Pasek; Ni Luh Sri Kasih (Universitas Pendidikan Ganesha, 2021)
The high level of competition makes companies compete to retain and win the market competition, one of the strategies are granting price discounts. This was an experimental study that aims to analyze the differences between males and females' intention for online purchase by given the price discount framing conditions, namely percentage saving and absolute saving. The participants in this study were 80 participants. This study was an experimental study since it involved the symptoms had to be investigated. The design of the study was a 2X2 factorial design. A case questionnaire was used for the data collection. The data were analyzed by using 2-ways ANOVA statistical analysis. The study reveals that (1) there is a difference in online purchase intention between those given the percentage saving condition and those given the absolute saving condition, (2) there is a difference in purchase intention between males and females. The consumers have different assumptions about the two types of discount framing even though they both have the same meaning. This should be a concern for retailers in providing sales promotions, especially for discounts because based on the results of this study it is found that discount framing with absolute savings had a slightly stronger effect on purchase intention than percentage saving.